1993
DOI: 10.1089/jop.1993.9.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antiglaucoma Drugs on Ocular Blood Flow in Ocular Hypertensive Rabbits

Abstract: Antiglaucoma drugs were studied systematically on the ocular blood flow in ocular hypertensive rabbits. As expected, pilocarpine, clonidine and acetazolamide were all found to increase the ocular blood flow in the retina and choroid.However, their use in the clinics was much less than the /9-blockers, such as Ltimolol, levobunolol, betaxolol and metipranolol. It was surprising to find that all non-specific and /?]-specific adrenergic blockers decreased the ocular blood flow in ocular hypertensive rabbits. If t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…The potency differ ence in the two drugs may be due to the num bers of nitrate esters per molecule (GTN 3 vs. nipradilol 1) or due to the efficacy of the de nitrification enzyme [17], Nipradilol-induced vasodilatation was seen 15 s after the injec tion; the ocular blood flow is expected to be increased. The blood flow increase may be one of the mechanisms underlying the reduc tion of the intraocular pressure [4], In fact, the relationship between ocular blood (low and decreased ocular pressure is suggested from results obtained in anesthetized rabbits [3],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potency differ ence in the two drugs may be due to the num bers of nitrate esters per molecule (GTN 3 vs. nipradilol 1) or due to the efficacy of the de nitrification enzyme [17], Nipradilol-induced vasodilatation was seen 15 s after the injec tion; the ocular blood flow is expected to be increased. The blood flow increase may be one of the mechanisms underlying the reduc tion of the intraocular pressure [4], In fact, the relationship between ocular blood (low and decreased ocular pressure is suggested from results obtained in anesthetized rabbits [3],…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cholinergic agonists and p-and cti-adrenoceptor antagonists, attention is thus directed to NO donors as new therapeutics of glaucoma or ocular hypertension. Mechanisms of ocular hypotensive action include a decrease in aqueous humor formation and an increase in outflow or drainage of the humor and in ocu lar blood flow [4], Nipradilol, recently devel oped as an antianginal [5,6] or systemic hypo tensive agent [7], has an NO? moiety in its chemical structure, induces vasodilatation by activating soluble guanylate cyclase, and in creases the production of cyclic guanosine monophosphate (GMP) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Certain eye diseases such as glaucoma, ischemic retinopathy, and age-related macular degeneration are related to the malfunction of ocular circulation/blood flow (1)(2)(3)(4)(5)(6)(7). Therefore, the search for drugs that can improve ocular blood flow, particularly in retina and choroid, is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been debated whether these agents also act directly on the retinal circulation to change retinal blood flow. Although the influence of β-adrenergic antagonists on retinal artery diameter has been studied in animals, in-vivo and in a clinical setting, the results remain controversial with some reports suggesting that some β-and the β " -selective adrenergic antagonists decreased ocular blood flow (Yan and Chiou, 1987 ;Chiou and Chen, 1993), whereas other studies have indicated increased blood flow (Grunwald, 1986). This is an important issue as if an IOP reducing agent also causes a reduction in blood flow to the retina then its overall clinical value would have to be in question, especially as there is much evidence that implicates reduced blood flow as another major factor in some glaucoma pathologies (Flammer, 1996).…”
Section: Introductionmentioning
confidence: 99%